Does topical application of bupivacaine (Marcaine)to skin graft donor site have any effect on moriarty sign? (2000)
Moriarty sign designates that when split skin donor site is more painful than recipient site,good graft take is likely. This prospective study was designed for the dual purpose of confirming the validity of Moriarty sign and to determine if bupivacaine topical anaesthetic application to split skin donor site will influence the sign. The difference in response to pain indicated by Moriarty sign between patients that had topical analgesic treatment and those that did not was statistically significant from day one to day five post operatively. Routine application of long acting topical analgesic to donor site is advocated ( Nig J Surg Res 2000;2:131-134)